The Efforts of the Satlantas Patrol Unit in Preventing Traffic Violations in the Banjarmasin Police Area During the Covid-19 Pandemic - Ghalib Putra (Police Studies Review, 2021)
While the COVID 19 pandemic is still roaming around the globe, there are several main changes that happened in Indonesia as well. These changes could be found throughout daily life such as the academics, jobs and humanity and its usage or function itself. With the many changes that happened abruptly because of the virus, the researcher chose “upaya unit patroli satlantas dalam mencegah pelanggaran lalu lintas di wilayah polresta banjarmasin pada masa pandemi COVID-19.” as the title in hope that this thesis can brought new knowledge about numerous ways and efforts that have been done and will be done by to avoid any traffic violations by the patrol units during this COVID-19 pandemic that would be rather easier or tougher hence twice the efforts than the usual ways before pandemic. The researcher of this thesis on a whole matter will be using qualitative methods to analyze the collected data and interviews, the researcher would as well spread a questioner with an open answer which can be filled according to the intended people, the observation around Polresta Banjarmasin street have been done in the span of 2-3 months that is already calculated strictly and is enough to retrieve the data intended. There are several factors that affect the mentioned problem, such as internal and external factors on the other hand countable supporting efforts to help the effectiveness of the patrol units to have a smooth and perfect execution of their plans and ways, this is thoroughly done by ceasing the usage of activities in the main street of Banjarmasin, which is Ahmad Yani street due to the COVID-19 pandemic and this will ease the job to be worked out though not forgetting the existence of several internal and external factors.